1993
DOI: 10.1093/ajcn/58.4.468
|View full text |Cite|
|
Sign up to set email alerts
|

Metabolic evidence that deficiencies of vitamin B−12 (cobalamin), folate, and vitamin B−6 occur commonly in elderly people

Abstract: Measurements of the serum concentrations of the metabolites homocysteine, cystathionine, methylmalonic acid, and 2-methylcitric acid, which accumulates when vitamin B-12-, folate-, and vitamin B-6-dependent enzymatic reactions are impaired, should provide a better indication of intracellular deficiency of these vitamins. We measured the serum concentration of these vitamins and the four metabolites in 99 healthy young people, 64 healthy elderly subjects, and 286 elderly hospitalized patients. A low serum vitam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
153
1
2

Year Published

1995
1995
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 299 publications
(167 citation statements)
references
References 30 publications
11
153
1
2
Order By: Relevance
“…Folate and vitamin B 12 status, particularly in the elderly, is currently the subject of considerable debate, primarily Iron, folate and vitamin B 12 status KE Charlton et al because re®ned biochemical techniques estimate the prevalence of tissue de®ciency, without the presence of anaemia, to be higher than the prevalence detected by measuring serum or blood cell concentration of the vitamins (Joosten et al, 1993;Lindenbaum et al, 1994); such suboptimal status at the biochemical level has been associated with signi®cant neuropsychiatric damage including impairment in cognitive function Healton et al, 1991). Moreover, similar suboptimal status of both vitamins, together with vitamin B 6 , has been associated with elevated serum homocysteine concentration (Stabler et al, 1988), the latter being increasingly accepted as an independent and major risk factor for coronary, peripheral and cerebrovascular disease (Clarke et al, 1991;Kang et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Folate and vitamin B 12 status, particularly in the elderly, is currently the subject of considerable debate, primarily Iron, folate and vitamin B 12 status KE Charlton et al because re®ned biochemical techniques estimate the prevalence of tissue de®ciency, without the presence of anaemia, to be higher than the prevalence detected by measuring serum or blood cell concentration of the vitamins (Joosten et al, 1993;Lindenbaum et al, 1994); such suboptimal status at the biochemical level has been associated with signi®cant neuropsychiatric damage including impairment in cognitive function Healton et al, 1991). Moreover, similar suboptimal status of both vitamins, together with vitamin B 6 , has been associated with elevated serum homocysteine concentration (Stabler et al, 1988), the latter being increasingly accepted as an independent and major risk factor for coronary, peripheral and cerebrovascular disease (Clarke et al, 1991;Kang et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…In unison with these proposals, it is of interest that in the present study serum ferritin levels below 15mg/l were uncommon in men and found only in 5 of the women. Serum ferritin is an acute phase protein and is typically elevated in infection, in¯ammation and malignancy (Joosten et al, 1993;Bothwell et al, 1979;Worwood, 1986). When iron de®ciency therefore coexists with chronic disease serum ferritin may be falsely raised and iron de®ciency may remain undiagnosed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estimates among the elderly vary widely; from 5% (based upon a low serum vitamin B 12 concentration) among institutionalized elderly adults in Germany, The Netherlands and Belgium (32) to 46% (based on multiple criteria including serum vitamin B 12 and methylmalonic acid (MMA)) among institutionalized elderly adults in the UK (33) . The impact on estimates of prevalence of using different criteria of deficiency can be illustrated by adapting data presented for a UK cohort of elderly adults (34) .…”
Section: Prevalencementioning
confidence: 99%
“…Following the early studies that demonstrated the basic relationship between vitamin B 12 and MMA in man (Gompertz et al, 1967;Chanarin et al, 1973;Norman et al, 1982;Carmel, 2000), and which established reliable assay techniques for MMA (Stabler et al, 1986), were a number of key studies showing a surprisingly high prevalence of raised MMA levels in the plasma of older people, where it appeared to provide a more reliable indicator of functional vitamin B 12 status than serum or plasma vitamin B 12 concentrations per se (Lindenbaum et al, 1988;Rasmussen et al, 1989;Moelby et al, 1990;Joosten et al, 1993;Allen & Casterline, 1994;Lindenbaum et al, 1994;Koehler et al, 1996;Baik & Russell, 1999;Bjorkegren & Svardsudd, 1999;Herrmann et al, 2000). Clearly, the ageing process in itself, and the increasing prevalence of age-related medical conditions that impair vitamin B 12 absorption, both increase the probability that people will become vitamin B 12 -deficient as they grow older.…”
Section: Introductionmentioning
confidence: 99%